Economic analysis on herbicides management systems affecting oil palm production / Muhammad Hazim Yazid - Yazid, Muhammad Hazim (Faculty of Plantation and Agrotechnology, 2019)
Oil palm plantation is the biggest plantation in Malaysia and give huge impact to the economic and income to our country. In plantation, the major problem affecting to the oil palm production is the number of weed growth and this can cause competitions based on nutrients, sunlight and water between main crop and weed. There are several techniques to remove the weed but the easiest way to remove the weed is using chemical herbicide. The herbicides are widely used in the plantation because it can gives cost effective to the company and high succession of killing the weeds. This study focusing on the economic analysis of herbicides management systems affecting oil palm production. The objective of this study to investigate the economic analysis of different herbicide management systems affecting the productivity of oil palm. The study was done at Tradewinds Plantation and Jaya Baru Plantation which both plantations were using different ways in herbicides management systems for their plantation. The data for this study was collected by using interview (face to face session) and secondary data collection method starting from year 2015 until half year of 2018. Economic analysis was study in relation between factors in herbicides management systems stated in this study. The result in this study was analyzed by using descriptive data, benefit cost ratio and t-test by using SPSS (statistical). From this study, it was shown that the herbicides management systems applied by Tradewinds Plantation is better economically as the result were analyzed through benefit cost ratio and t-test analysis. Thus, it was recommended by all farmer and plantations to use the systems applied by Tradewinds Plantation because it can gives higher income to the plantation. Lastly, a good herbicides management systems is important in the management of a plantation because it can helps the plantation to achieve higher productivity